2015
DOI: 10.1007/s00414-015-1272-5
|View full text |Cite
|
Sign up to set email alerts
|

Palatal rugae patterning in a modern Indonesian population

Abstract: The palatal rugae patterns provide potentially useful supplementary information to establish the identity of an individual, but only when appropriate antemortem data are available. For this purpose, it is suggested that optical 3D oral/dental scanning is used to retain the data on the rugal and oropalatal patterns. Suitable pattern recognition methods may also reduce the potential effects of rugae modification in time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
4
11
0
2
Order By: Relevance
“…The palatal rugae patterns in the present study were individualized and unique for each subject. This agrees with previous studies in Jordan [28], India [13], and Indonesia [29] where none of the patterns were identical or alike. Furthermore, no bilateral symmetry was observed in any individual.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The palatal rugae patterns in the present study were individualized and unique for each subject. This agrees with previous studies in Jordan [28], India [13], and Indonesia [29] where none of the patterns were identical or alike. Furthermore, no bilateral symmetry was observed in any individual.…”
Section: Discussionsupporting
confidence: 93%
“…The same finding was observed by Simmons et al [30], Poojya et al [4], Indira et al [13] and Syed et al [32]. However, this contradicts the finding reported by Suhartono et al [29] where palatal rugae in Indonesian females were slightly higher than males.…”
Section: Discussionsupporting
confidence: 47%
“…In addition, there was no significant difference among different sagittal skeletal malocclusion groups in terms of the number of PPR and SPR on either sides of the palate. These findings are consistent with those reported by Suhartono et al [2] As a result, PPR and SPR showed symmetric distribution in terms of their numbers on either sides of the palate among different skeletal malocclusion groups.…”
Section: Discussionsupporting
confidence: 93%
“…[1] The number, shape, width, height, and location of palatal rugae vary from the left side of the palate to the right side as well as from one person to another, and are unique to every individual. [2] Recent studies have suggested that palatal rugae could be used in forensic identification. [3,4] Palatal rugae remain stable throughout life and therefore they are commonly used by dental clinicians as a reference point to evaluate the extent of tooth movement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation